An Analysis of Instagram Posts about Genioplasty. Issue 3 (3rd July 2021) - Ayranci, Ferhat; Buyuk, Suleyman Kutalmis; Kahveci, Kadircan; Sunar, Cagla
Abstract: Social media platforms have become popular in recent years and are good ways frequently used to get information in medicine and dentistry. The purpose of this study was to evaluate the accuracy and quality of uploaded Instagram posts with #genioplasty and #chinsurgery hashtags. The first 100 posts were selected for #genioplasty and #chinsurgery hashtags and analyzed. The type of posts, posts' purpose, the source of posts, the number of likes and comments were recorded. Fifty-three posts; 11 posts in #genioplasty and 42 posts in #chinsurgery, were irrelevant and the remaining 147 posts were evaluated. The number of comments of the posts uploaded about patient experience in #genioplasty post was statistically higher than others ( p = 0.001). A statistically significant difference was found in the number of comments about preoperative-postoperative information in #chinsurgery posts ( p = 0.010). The other parameters did not show a significant difference ( p > 0.05). Instagram is an inappropriate social media platform for individuals to get information about genioplasty and may give more misleading and incorrect information. The patients should be guided to reach the correct sources of information on social media platforms.